Penerapan Model Direct Instructions Untuk Meningkatkan Hasil Belajar Penjaskes - Saiful Anam (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2016)
Abstract: Application Instructions Direct Model to Improve Learning Outcomes PE. This study aims to determine the effectiveness of the implementation of Direct models Instructions in improving the process and learning outcomes of students of class VII B SMP Negeri 4 Blitar. Classroom action research for two cycles with research subjects totaling 34 students. Instruments of data collection using observation sheet teachers and students learning activities, tests, field notes, and documentation. Data were analyzed with the following steps: data reduction, exposure data, and drawing conclusions. Results showed through the application of models direct instructions from the first cycle to the second cycle showed increased student learning outcome.Abstrak: Penerapan Model Direct Instructions untuk Meningkatkan Hasil Belajar Penjaskes. Penelitian ini bertujuan untuk mengetahui keefektifan penerapan model Direct Insructions dalam meningkatkan proses dan hasil belajar siswa kelas VII B SMP Negeri 4 Blitar. Penelitian tindakan kelas selama dua siklus dengan subyek penelitian berjumlah 34 siswa.Instrumen pengumpulan data menggunakan lembar observasi kegiatan pembelajaran guru dan siswa, tes, catatan lapangan, dan dokumentasi. Data dianalisis dengan langkah-langkah: reduksi data, paparan data, dan penarikan kesimpulan. Hasil penelitian menunjukkan melalui penerapan model direct instructions dari siklus pertama ke siklus kedua menujukkan peningkatan hasil belajar siswa meningkat.